Agriculture, Nutrition, and Health (ANH) Academy and ANH Academy Week Conference provide a unique, interdisciplinary conference and community to engage stakeholders around ANH - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
Influence of the ANH Academy Week conference activities was described in the mid-term evaluation (available upon request) of the London School of Hygiene and Tropical Medicine (LSHTM)-led project called Innovative Methods and Metrics for Agriculture and Nutrition Actions (IMMANA), which facilitates the ANH Academy. A4NH co-leads the annual conference.